2013
DOI: 10.1002/ange.201302024
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐Catalyzed Isocyanide‐Alkyne Cycloaddition: A General and Practical Method to Oligosubstituted Pyrroles

Abstract: Ag2CO3 macht den Unterschied: Die Übergangsmetall‐katalysierte Cycloaddition von Isocyaniden mit nichtaktivierten endständigen Alkinen wurde mit Ag2CO3 als einzigartigem und robustem Katalysator erreicht (siehe Schema). Die Reaktion ist sehr effizient, ermöglicht die Umsetzung einer Vielzahl endständiger und interner Alkine ohne Basen und Liganden und ergibt präparativ nützliche, mehrfach substituierte Pyrrole in hohen Ausbeuten. EWG=elektronenziehende Gruppe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The pioneering works of Yamamoto and de Meijere in 2005 opened up the copper‐catalyzed alkyne‐isocyanide [3+2] cycloaddition reactions, where the phosphine‐catalyzed reaction provided the regiodivergent synthesis of highly substituted pyrroles (Scheme a). In 2013, the groups of Bi and Lei independently reported the silver‐catalyzed alkyne‐isocyanide [3+2] cycloaddition reactions, expanding the alkyne substrate scope to terminal alkynes . Mechanistically, whereas the cationic phosphonium and the anionic carbanion intermediate species were postulated for the Lewis basic phosphine catalysts, the formation of C‐metallated isocyanides has been proposed by a recent experimental and theoretical study .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pioneering works of Yamamoto and de Meijere in 2005 opened up the copper‐catalyzed alkyne‐isocyanide [3+2] cycloaddition reactions, where the phosphine‐catalyzed reaction provided the regiodivergent synthesis of highly substituted pyrroles (Scheme a). In 2013, the groups of Bi and Lei independently reported the silver‐catalyzed alkyne‐isocyanide [3+2] cycloaddition reactions, expanding the alkyne substrate scope to terminal alkynes . Mechanistically, whereas the cationic phosphonium and the anionic carbanion intermediate species were postulated for the Lewis basic phosphine catalysts, the formation of C‐metallated isocyanides has been proposed by a recent experimental and theoretical study .…”
Section: Methodsmentioning
confidence: 99%
“…Based on our experimental observations on the 1,2‐migration of electron‐withdrawing groups, it is reasonable to assume two different mechanistic pathways of 2 H ‐pyrroles (Figure ). When the sp 3 ‐carbon of 2 H ‐pyrrole is substituted with an electron‐withdrawing group and a hydrogen, the preferential reaction pathway involves 1,5‐hydrogen shift to provide pyrroles with two EWGs at the 2‐ and 4‐carbon atoms (Figure a) . The replacement of hydrogen at the sp 3 ‐carbon of 2 H ‐pyrrole with smaller substituents such as a methyl group provides the inert structure of 2 H ‐pyrrole with a smaller bond angle for MeO 2 C–C–CH 3 that is free from the bond migration.…”
Section: Methodsmentioning
confidence: 99%
“…72 In 2013, our group overcame this difficulty using silver catalysis, thereby establishing a practical approach for accessing pyrroles 19 (Scheme 17b). 73 After extensively screening the reaction conditions, we found that Ag 2 CO 3 in hot 1,4-dioxane was a suitable system for the synthesis of pyrroles. A variety of terminal alkynes, including aryl, heteroaryl, alkyl, cyclopropyl, alkynyl, hydroxyalkyl, alkenyl, alkoxy, and acetyl acetylenes, smoothly underwent cycloaddition with ethyl isocyanoacetate to afford the desired pyrroles 19 in excellent yields (Scheme 18).…”
Section: Coupling Of Terminal Alkynes With Isocyanidesmentioning
confidence: 99%
“…During our preparation of this manuscript, Echavarren and Gaydou reported another chemoselective reaction of terminal alkynes with trimethylsilyl azide (TMSÀN 3 ) using gold catalysis, affording tetrazoles (Figure 1 b). [6] Inspired by Jiaos pioneering work and by our long-standing interest in developing transition-metal-catalyzed organic reactions, [7] we herein wish to report an unprecedented chemo-and regioselective hydroazidation of ethynyl carbinols. A general and efficient method to access 2-azidoallyl alcohols has thus been developed (Figure 1 c).…”
mentioning
confidence: 99%